2024
DOI: 10.1001/jamanetworkopen.2024.0680
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Patient Portal Use Among Adults With Chronic Conditions

Esther Yoon,
Scott Hur,
Lauren Opsasnick
et al.

Abstract: ImportanceDisparities in patient access and use of health care portals have been documented. Limited research has evaluated disparities in portal use during and after the COVID-19 pandemic.ObjectiveTo assess prevalence of health care portal use before, during, and after the most restrictive phase of the pandemic (2019-2022) among the COVID-19 & Chronic Conditions (C3) cohort and to investigate any disparities in use by sociodemographic factors.Design, Setting, and ParticipantsThis cohort study uses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…The prevalence of IMSU (39.43% with the provincial eld survey data) reported in our results was similar to the latest data reported in Health Information National Trends Survey (HINTS) in the U.S. (39.3%), and were consistent with prior literature on digital health inequities among patients with inferior demographic (e.g., gerontal patients) and socio-economic factors (e.g., educated at basic education level), as well as increased IMSU accessed among patients with poorer health status (e.g., suffering multi chronic diseases) , but not for gender in this study [13,20,25,[27][28][29][30]. We also found that, the respondents from the national online survey with superior demographic and socio-economic factors, but poorer health status than those from the provincial eld survey.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The prevalence of IMSU (39.43% with the provincial eld survey data) reported in our results was similar to the latest data reported in Health Information National Trends Survey (HINTS) in the U.S. (39.3%), and were consistent with prior literature on digital health inequities among patients with inferior demographic (e.g., gerontal patients) and socio-economic factors (e.g., educated at basic education level), as well as increased IMSU accessed among patients with poorer health status (e.g., suffering multi chronic diseases) , but not for gender in this study [13,20,25,[27][28][29][30]. We also found that, the respondents from the national online survey with superior demographic and socio-economic factors, but poorer health status than those from the provincial eld survey.…”
Section: Discussionsupporting
confidence: 91%
“…However, the respondents with superior demographic (e.g., aged below 60 years old) and socio-economic factors (e.g., higher annual disposable income) from the national online survey were more likely to be deeply involved in IMSU (e.g., mental diseases: 374 times with 10.44%; telediagnosis: 378 times with 8.23%), which were consistent with previous studies [30][31][32][33][34]. Prior research has also indicated that the patterns of IMSU would be deepen in the patients with a chronic condition, nevertheless, in this study, patients suffering chronic diseases were less accessed to IMSU that those not suffering (35.59% vs. 40.56%) based on the provincial eld survey data, and patients suffering chronic diseases accessed to IMSU at a high frequency was lower than that at a low frequency (29.86% vs. 34.45%) based on the national online survey data [13,20,32,[35][36][37][38][39].…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Digital determinants of health (DDoH), including access to technological tools, digital health literacy, and internet access, function independently as barriers to health, and a lack of these aspects negatively impacts health outcomes and patient experiences [ 6 , 7 ]. Data from the COVID-19 and Chronic Conditions cohort analyzing portal use suggested that the restrictive phase of the epidemic widened disparities in health literacy [ 8 ]. Analysis of the Health Information National Trends Survey demonstrated that minority populations had less access to an electronic health record compared to White and non-Hispanic populations [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In an assessment of patients admitted to a general medicine service, low eHealth literacy was associated with less awareness, use, and perceived usefulness of portals [ 10 ]; however, further investigation of the role of eHealth literacy and DDoH in a nationwide, multilanguage survey is needed. Assessment of enablers and barriers across health care–seeking populations may serve to address extant digital health disparities and mitigate disparity expansion that may occur with public health emergencies [ 11 ]. To enhance patient engagement with digital health technologies and solutions, assessment of individual factors of DDoH, including digital health literacy, has been purported to be the first step to enabling access to these digitized forms of health care [ 12 ].…”
Section: Introductionmentioning
confidence: 99%